(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Objectives of the study include answer to the research question or to the hypothesis framed. Present study was conducted to evaluate the therapeutic effect of Shilajithu loha rasayana in reducing the affliction of Basti marma in patients with Prameha/diabetic nephropathy, also to evaluate the therapeutic effect of Shilajithu loha rasayana in reducing the blood sugar level in patients suffering from affliction of Basti marma in Prameha/diabetic nephropathy. Design: Study Type: Interventional, Estimated enrolment: 30 participants, Allocation: Non-Randomized, Endpoint Classification: Efficacy Study, Intervention Model: Single Group Assignment, Primary Purpose: Treatment, Masking: Open Label. Participants: From October 2019 to January 2020, 30 patients of affliction of Basthi marma in Prameha/ diabetic nephropathy having symptoms of diabetic nephropathy (microalbuminuria, reduced eGFR, raised cystatin-c) with a minimum of 5yrs history of diabetes are taken up for the study. Intervention: Kosta shodhana on day 1: 20ml of Eranda taila added with equal amount of Shunthi kashaya is orally administered during early morning in empty stomach. Day 2 to 22: Shilajithu loha rasayana is orally administered half an hour before breakfast, in a dose of 12g with warm water. Patient was advised diabetic diet and to do brisk walking/jogging or light exercise for 45 minutes daily during the course of treatment. Results: Shilajithu loha rasayana was successful in improving renal functions by increasing the glomerular filtration rate and reducing cystatin-c in patients also was successful in reducing fasting blood sugar and symptoms of Prameha which was justified statistically with p value <0.001. Conclusion: Shilajithu loha rasayana was successful in increasing the renal function and reducing symptoms of Prameha.